Programmes to support transitions in community care for children with complex care needs: a scoping review. Issue 7 (8th July 2022) - Breneol, Sydney; Doucet, Shelley; McIsaac, Jessie-Lee; Riveroll, Angela; Cassidy, Christine; Charlton, Patricia; McCulloch, Holly; McKibbon, Shelley; Luke, Alison; Splane, Jennifer; Curran, Janet A
Abstract : Objective: This scoping review aimed to map the range of programmes in the literature to support children and youth with complex care needs and their families during transitions in care in the community. Design: A scoping review of the literature. Context: This review included programmes that supported the transition in care to home and between settings in the community. Data sources: We implemented our strategy to search five databases: (1) PubMed; (2) CINAHL; (3) ERIC; (4) PyscINFO and (5) Social Work Abstracts. The search was last implemented on 29 April 2021. Study selection: Our search results were imported into Covidence Systematic Review Software. First, two reviewers assessed titles and abstracts against our eligibility criteria. Relevant articles were then retrieved in full and reviewed by two reviewers for inclusion. Disagreements were resolved by a third reviewer. Data extraction: Relevant data were extracted related to population, concept, context, methods and key findings pertinent to our review objective. Results: A total of 2482 records were identified. After our two-stage screening process, a total of 27 articles were included for analysis. Articles ranged in the type of transitions being supported and target population. The most common transition reported was the hospital-to-home transition. Intervention components primarily consisted of care coordination using a teams-based approach. The most reported barriers and enablers to implementing these transition care programmes were related to physical opportunities. Limitations: Included articles were limited to English and French. Conclusions: This review identified important gaps within the literature, as well as areas for future consideration to ensure the effective development and implementation of programmes to support children and youth with complex care needs during transitions in care.